Function Overlap

Geometry Level 2

What value of C C would make the graph of y = cos ( x + C ) y=\cos (x+C) be equal to y = sin x y=\sin x ?

π 2 -\frac \pi 2 π 2 \frac \pi 2 Both of the others

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Poca Poca
Jul 3, 2018
  1. Here's a geometric approach: Consider a right angled triangle A B C ABC with its right angle at C C . Because the sum of the interior angles in a triangle is always π \pi , we have β = π 2 α \beta = \frac{\pi}{2} - \alpha . By definition, sin ( β ) = A C A B \sin(\beta) = \frac{\overline{AC}}{\overline{AB}} and cos ( α ) = A C A B \cos(\alpha)=\frac{\overline{AC}}{\overline{AB}} . Thus, cos ( α ) = sin ( β ) = sin ( π 2 α ) = sin ( π ( π 2 α ) ) = sin ( α + π 2 ) \cos(\alpha)=\sin(\beta)=\sin(\frac{\pi}{2} - \alpha) = \sin(\pi - (\frac{\pi}{2} - \alpha))=\sin(\alpha + \frac{\pi}{2}) . If we swap the parameters, the signs change and hence C = π 2 C=-\frac{\pi}{2} .

  2. Alternatively, we may assume that one of the given answers is correct and use the addition formula for cosine: cos ( x π 2 ) = cos x cos ( π 2 ) sin x sin ( π 2 ) = cos x 0 sin x ( 1 ) = sin x \cos(x-\frac{\pi}{2})=\cos x \cdot \cos \left(-\frac{\pi}{2}\right) - \sin x \sin \left(\frac{\pi}{2}\right) = \cos x \cdot 0 - \sin x \cdot (-1) = \sin x will turn out to be the correct answer.

  3. Using the complex definition of the cosine, we may also show this result using that e i ( 0.5 π ) = cos ( 0.5 π ) + i sin ( 0.5 π ) = i e^{i(-0.5\pi)}=\cos(-0.5\pi)+i\sin(-0.5\pi)=-i and e i ( 0.5 π ) = cos ( 0.5 π ) + i sin ( 0.5 π ) = i e^{i(0.5\pi)}=\cos(0.5\pi)+i\sin(0.5\pi)=i . We have

cos ( x 0.5 π ) = 1 2 ( e i ( 0.5 π ) + e i ( 0.5 π ) ) = 1 2 ( e i ( x 0.5 π ) + e i ( x 0.5 π ) ) = 1 2 ( e i ( x 0.5 π ) + e i ( 0.5 π x ) ) ) = 1 2 ( e i x e i ( 0.5 ) + e i 0.5 e i x ) = 1 2 ( i e i x + i e i x ) = 1 2 i ( i i e i x + i i e i x ) = 1 2 i ( e i x e i x ) = sin ( x ) \begin{aligned} \cos (x-0.5\pi) &= \frac{1}{2} \left( e^{i\cdot (-0.5\pi)} + e^{-i\cdot (-0.5\pi)} \right)\\ &= \frac{1}{2} \left( e^{i\cdot (x-0.5\pi)} + e^{-i\cdot (x-0.5\pi)} \right)\\ &= \frac{1}{2} \left( e^{i\cdot (x-0.5\pi)} + e^{i\cdot (0.5\pi-x))} \right)\\ &= \frac{1}{2} \left( e^{ix} \cdot e^{i\cdot (-0.5)} + e^{i\cdot 0.5}\cdot e^{-ix} \right)\\ &= \frac{1}{2} \left( -ie^{ix} + ie^{-ix} \right)\\ &= \frac{1}{2i} \left( -i\cdot i\cdot e^{ix} + i\cdot i\cdot e^{-ix} \right)\\ &= \frac{1}{2i} \left( e^{ix} - e^{-ix} \right)\\ &= \sin(x) \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...